Protection Consumer to Perspective Brand Manipulation Maqashid Syariah (Shopee Marketplace Case Study) - Syafitri, Rizka; Sativa, Annisa (LEGAL BRIEF, 2025)
Brand manipulation is one of the most common violations of intellectual property rights in marketplaces, including Shopee. This practice harms consumers and original brand owners by causing confusion, lowering product quality in the market, and threatening user safety. This study aims to analyze the factors causing brand manipulation to protect consumer rights based on the consumer Protection Law (UUPK) and explore the application of Maqashid Syariah justice values. This study uses a library research method with a descriptive qualitative approach. A statute approach is used to analyze relevant regulations, such as Law No. 8 of 1999 on Consumer Protection and Law No. 20 of 2016 on Trademarks and Geographical Indications. . Research suggests that brand manipulation results from a number of major factors: a lack of consumer knowledge of the original, a profitable economic advantage for business owners, a lack of legal supervision and enforcement, tight market competition, and a lack of clear quality standards. This dishonest act costs the consumer dearly. Maqashid sharia views all Islamic laws as aimed at keeping the five main things in human life: religion (ad-din), soul (an-nafs), reason (al-'aql), descendants (an-nasl), and treasure (al-mal). This points out that the importance of increased surveillance, more stringent law enforcement, and education of consumers to be more aware of products circulating in the marketplace. Shopee as an e-commerce platform also has a crucial role in ensuring that the sellers on the platform comply with consumer protection regulations.